Pig manure for fish ponds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
With the intensification of pig production in some countries and the consequent problem of disposing manure, there is considerable interest in the traditional Chinese method of raising fish in ponds by feeding them with pig manure. Researchers at...